Health-related quality-of-life results for pembrolizumab versus chemotherapy in advanced, PD-L1-positive NSCLC (KEYNOTE-024): a multicentre, international, randomised, open-label phase 3 trial. Issue 12 (December 2017) - Brahmer, Julie R; Rodríguez-Abreu, Delvys; Robinson, Andrew G; Hui, Rina; Csőszi, Tibor; Fülöp, Andrea; Gottfried, Maya; Peled, Nir; Tafreshi, Ali; Cuffe, Sinead; O'Brien, Mary; Rao, Suman; et al.
Summary: Background: In the phase 3 KEYNOTE-024 trial, treatment with pembrolizumab conferred longer progression-free survival than did platinum-based therapy in patients with treatment-naive, advanced non-small-cell lung cancer (NSCLC) with a programmed cell death-ligand 1 (PD-L1) tumour proportion score of 50% or greater (PD-L1-positive). Here we report the prespecified exploratory endpoint of pembrolizumab versus chemotherapy on patient-reported outcomes (PROs). Methods: In this multicentre, international, randomised, open-label, phase 3 trial, we recruited patients with treatment-naive, stage IV NSCLC in 102 sites in 16 countries. Eligible patients had measurable disease (per RECIST version 1.1) and an Eastern Cooperative Oncology Group (ECOG) performance status 0 or 1. Patients were randomly assigned (1:1) via an interactive voice response system and integrated web response system to receive either pembrolizumab 200 mg every 3 weeks (35 cycles) or investigator-choice platinum-doublet chemotherapy (4–6 cycles or until documented disease progression or unacceptable toxicity). Randomisation was stratified according to geography, ECOG performance status, and histology. PROs were assessed at day 1 of cycles 1–3, every 9 weeks thereafter, at the treatment discontinuation visit, and at the 30-day safety assessment visit using the European Organisation for the Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 items (QLQ-C30), the EORTC Quality of Life Questionnaire Lung Cancer 13 items (QLQ-LC13), and the European Quality of Life 5 Dimensions-3 Level (EQ-5D-3L) questionnaire. The key exploratory PRO endpoints (analysed for all patients who received at least one dose of study treatment and completed at least one PRO instrument at at least one timepoint) were baseline-to-week-15 change in the QLQ-C30 global health status (GHS)/quality-of-life (QOL) score and time to deterioration of the composite of cough, chest pain, and dyspnoea in the QLQ-LC13. This study is registered withClinicalTrials.gov, numberNCT02142738, and is ongoing but no longer enrolling patients. Findings: Between Sept 19, 2014, and Oct 29, 2015, 305 patients were randomly assigned to pembrolizumab (n=154) or chemotherapy (n=151). Three patients in each group did not complete any PRO instruments at any timepoints, and so 299 patients were included in the full analysis set. Of these patients, one in each group did not complete any PRO instruments before week 15, and so were not included in analyses of change from baseline to week 15. PRO compliance was greater than 90% at baseline and approximately 80% at week 15 for both groups. Least-squares mean baseline-to-week-15 change in QLQ-C30 GHS/QOL score was 6·9 (95% CI 3·3 to 10·6) for pembrolizumab and −0·9 (−4·8 to 3·0) for chemotherapy, for a difference of 7·8 (2·9 to 12·8; two-sided nominal p=0·0020). Fewer pembrolizumab-treated patients had deterioration in the QLQ-LC13 composite endpoint than did chemotherapy-treated patients (46 [31%] of 151 patients vs 58 [39%] of 148 patients). Time to deterioration was longer with pembrolizumab than with chemotherapy (median not reached [95% CI 8·5 to not reached] vs 5·0 months [3·6 to not reached]; hazard ratio 0·66, 95% CI 0·44–0·97; two-sided nominal p=0·029). Interpretation: Pembrolizumab improves or maintains health-related QOL compared with that for chemotherapy, and might represent a new first-line standard of care for PD-L1-expressing, advanced NSCLC. Funding: Merck & Co.